Pretreatment platelet‐to‐lymphocyte ratio is associated with the response to first‐line chemotherapy and survival in patients with metastatic gastric cancer. Issue 1 (26th February 2017) - Wang, Jin; Qu, Jinglei; Li, Zhi; Che, Xiaofang; Liu, Jing; Teng, Yuee; Jin, Bo; Zhao, Mingfang; Liu, Yunpeng; Qu, Xiujuan
Abstract : Background: Several studies have shown that platelet‐to‐lymphocyte ratio (PLR) is a prognostic factor for various cancers. However, there is no study about the role of PLR in predicting response to first‐line chemotherapy of metastatic gastric cancer. Therefore, this study aimed to establish whether PLR is associated with the response to first‐line chemotherapy and survival in patients with metastatic gastric cancer. Methods: We enrolled 273 patients diagnosed with metastatic gastric cancer. The best cut‐off value of PLR to predict chemotherapeutic response was chosen by receiver operating characteristic (ROC) curve analysis. Prognostic significance was determined using the log‐rank test and multivariate Cox regression analysis. Results: Based on the cut‐off value of PLR, patients were divided into a low PLR group and high PLR group. In logistic regression analysis, the low PLR group had a significantly higher disease control rate than the high PLR group had (91.3 vs 76.1%, P =.002), and PLR was an independent risk factor for response to first‐line chemotherapy (odds ratio [OR]: 3.256; 95% confidence interval [CI]: 1.521‐6.969; P =.002). The low PLR group had significantly longer overall survival (OS) than the high PLR group had (13.4 vs 9.2 months; P =.020). Multivariate survival analysis showed that PLR was significantly associated with OS [hazard ratio (HR): 1.002; 95% CI: 1.000‐1.003; P =.020]. Conclusions: Pre‐treatment PLR is associated with the response rate to first‐line chemotherapy and survival outcomes in patients with metastatic gastric cancer.